PEMBATALAN AKTA JUAL BELI SAHAM YANG MENGAKIBATKAN CROSSHOLDING OLEH PENGADILAN - Mandai, Doris; Purwaningsih, Endang; Santosa, Irwan (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2023)
Cross Ownership in a limited liability company known as cross holding is a condition iwhere a limited liability company owns shares iissued by another ilimited liability icompany whose shares are directly or indirectly owned by the company, and vice versa The notary as a general official who makes ithe deed of isale and ipurchase ofishares imust understand the rules related to the transfer of shares, so as not to cause cancellation of the deed by the court. The problems raised in this thesis are what are the legal consequences of the cancellation of a Notary deed regarding the sale and purchase of shares resulting in crossholding by the court, how are the legal considerations of a court judge in declaring null and void a Notary deed. The purpose of this study is to analyze the legal consequences of the cancellation of a Notary deed resulting in Crossholding by the court, and to analyze the judgment of the court judge in declaring null and void a Notary deed. This research is a normative juridical research using a statutoryapproach and a case study approach. Data collection techniques were obtained by means oflibrary researchin the form of document studies. Data analysis uses qualitative analysis, then conclusions are drawn using deductive thinking methods. The judicial reason for the court to declare a notarial deed null and void is if the notary deed does not meet the objective and subjective requirements of an agreement. iThe legal iconsequence iof the icancellation of a Notary ideed by the court is theichange in the status and strength of proof of a Notary deedias an authentic deed to a private deed. Suggestions from this research are so that judges can make wise and fair decisions in handling every case, especially those relating to the cancellation of a notary deed